ON THE AMMONITE SUCCESSION IN THE JURASSIC-CRETACEOUS BOUNDARY BEDS OF THE MOSCOW SYNECLISE - Mitta V.V. (My University, 2004)
The succession of ammonite assemblages in the central regions of the Russian Platform from the Virgatites virgatus Zone (Middle Volgian Substage) to the Surites tzikwinianus Zone (Ryazanian Stage) is discussed. The analysis of the data available suggests a considerable gap between the Craspedites nodiger Zone, terminal in the Volgian Stage, and the Riasutlires rjasanensis Zone, basal in the Ryazanian Stage. Praresurites nikitini sp. nov. and Pseudocraspedites bogomolovi sp. nov. from the basal beds of the Ryazanian and Praetollia olivikorum sp. nov. from the unnamed unit above the top of the Volgian are described. The three genera to which these species belong are recorded for the first time from the Russian Platform. They allow a better correlation of the Jurassic-Cretaceous boundary beds within the Boreal Realm.
Keywords: ammonites; Jurassic-Cretaceous boundary; Moscow Basin; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская